Bilateral Papilledema with Sixth Cranial Nerve Palsy Complication: A Case Report - Septiani Nadra Indawaty; Lilis Khairani; Ahmad Ghiffari; Fera Yunita Rodhiaty; Hasmeinah Hasmeinah; Ibrahim Ibrahim (Universitas Muhammadiyah Palembang, 2026)
Papilledema is swelling of the optic disc due to increased intracranial pressure (ICP) which can cause neurological symptoms such as headache, nausea, vomiting, and progressive visual impairment and can lead to permanent blindness if not treated appropriately. This condition must be differentiated from disc edema due to other etiologies because it has a different pathophysiology and management. This case report discusses a 32-year-old woman who presented with complaints of blurred vision such as shadows in the left eye for five days, accompanied by frontal headache radiating to the retrobulbar, nausea, intermittent fever, and impaired eye movement. Ophthalmological examination showed decreased vision, limited mediolateral movement of both eyes indicating paresis of the sixth nerve, and fundoscopic images of bilateral blurred papilla borders with more severe swelling in the left eye accompanied by hard exudate. The patient was diagnosed with papilledema with diplopia ODS ec. paresis of the sixth nerve and was given supportive therapy in the form of cendo lyteers and mecobalamin as well as regular check-up education. This case emphasizes the importance of early detection of papilledema through history taking, clinical examination, and fundoscopy to prevent permanent visual complications and determine comprehensive and timely management.